The Influence of Entrepreneurship Education and Digitalization on The Entrepreneurial Interest of Youth at SMK TI BAZMA - Rattu, Afta Bintang Kautsar Fath; Kuraesin, Ecin; Hasnin, Hannisa Rahmaniar (Universitas Ibn Khaldun Bogor, 2025)
This study aims to determine the influence of entrepreneurship education and digitalization on students’ entrepreneurial interest at SMK TI BAZMA, both partially and simultaneously. A quantitative approach was employed, with data collected through questionnaires distributed to all students as respondents. The collected data were analyzed using validity tests, reliability tests, multiple linear regression, coefficient of determination, and hypothesis testing with both t-tests and F-tests. The results indicate that entrepreneurship education has a significant partial effect on entrepreneurial interest. In contrast, digitalization does not show a significant influence when tested separately. However, when analyzed simultaneously, both independent variables significantly affect students’ entrepreneurial interest. These findings highlight the essential role of entrepreneurship education in fostering students’ motivation to pursue entrepreneurship. Although digitalization does not show a strong partial effect, it remains a crucial component in supporting entrepreneurial learning. This study is expected to contribute to the development of educational strategies that nurture a new generation of entrepreneurs who are both innovative and adaptive to technological advancements